Les "enfants du hasard" ? - Jean-Hervé Jézéquel (Les éditions de la Maison des sciences de l'Homme, 2003)
This article stands out against the scholarly literature that describes schooling during the colonial era as an unequivocal movement that first concerned the most westernised and urbanised part of the African societies. It intends to point out the diversity that characterised the West African educated elite by exploring the different ways this elite entered the "White school". The paper also insists on the necessity to analyse the complex ways African societies appropriate the "White school". This paper is based on the study of the graduates from the William Ponty School, a French colonial institution that trained the best educated elite in French Speaking West-Africa.